2020
DOI: 10.1021/acs.biomac.0c00819
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity of Native Major Ampullate, Minor Ampullate, Cylindriform, and Flagelliform Silk Proteins in Solution

Abstract: The foundations of silk spinning, the structure, storage, and activation of silk proteins, remain highly debated. By combining solution small-angle neutron and X-ray scattering (SANS and SAXS) alongside circular dichroism (CD), we reveal a shape anisotropy of the four principal native spider silk feedstocks from Nephila edulis . We show that these proteins behave in solution like elongated semiflexible polymers with locally rigid sections. We demonstrated that minor ampullate and cylindr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…A recent study has shown that native spider silk proteins also presented specific secondary structure profiles in solution. [ 42 ] According with the authors, Flag proteins were partially folded and presented β‐turn conformational structures. Their results suggest that spider silk proteins in general behave in solution like elongated semiflexible polymers with locally rigid sections, agreeing with the multiple conformational structure found for rNcFlag2222.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study has shown that native spider silk proteins also presented specific secondary structure profiles in solution. [ 42 ] According with the authors, Flag proteins were partially folded and presented β‐turn conformational structures. Their results suggest that spider silk proteins in general behave in solution like elongated semiflexible polymers with locally rigid sections, agreeing with the multiple conformational structure found for rNcFlag2222.…”
Section: Discussionmentioning
confidence: 99%
“…Other aspects such as pH, ionic conditions, fiber spinning speed, and the presence of His tag may also have influenced the spinning process and the success of fiber assembly. [ 5,42,53,54 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on various nuclear magnetic resonance (NMR) methods, Asakura and co-workers [28,[46][47][48] suggested that 'the highly concentrated silk solution contained in the middle silk gland has residues in energetically favored conformations close to average random coil values, but forms a hydrogen-bonded network that keeps it in a repeated type II β-turn structure'. Other studies have also demonstrated predominantly random coil, helical or β-turn conformations in various native, recombinant or redissolved spidroin (spider silk protein) solutions [49][50][51][52][53][54][55][56][57].…”
mentioning
confidence: 99%